Cryo-laser and cryo-sclerotherapy guided by Augmented Reality - Miyake, R. K. (Phlebologie, 2014)
Background: This study is about CLaCS, a new technique to treat telangiectasias and feeder veins.Method: A series of 140 cases were treated under Augmented Reality guidance in a completely different way. Sclerosis was achieved by combination of thermal and chemical agents: laser and dextrose. Patients were classified according to two questions: presence of varicose veins and/or reflux on the saphenous vein; presence of telangiectasias and/or feeder veins (Score 9–1). Duplex ultra-sound and Augmented Reality (VeinViewer) were used to detect reflux and feeder veins, respectively. Feeder veins and telangiectasias were treated the same way, in the same procedure, by a combination of Nd:YAG 1064 nm with spot sizes of 6mm, 15 msec pulse and fluence of up to 80 J/cm2 followed by injection sclerotherapy of Dextrose 75%. Both techniques were done under forced air skin cooling (Cryo5). A thorough photodocumentation was done prior and after each procedure and results were obtained by comparing before and after photos on two iPads. Response to the treatment was rated on: total or partial improvement with patient satisfaction (Group 1); partial improvement or lack of resolution, without patient satisfaction (Group 2).Results: A total of 466 patients visited the clinic during the study and exclusion criteria left a total of 140 patients for analysis. Mean age of patients was 37 years (16 to 72), with prevalence of women (98 %). No allergic reactions, systemic reactions, skin burns, post-sclerotherapy mattings, infections or crustings were observed. Temporary ecchymosis were observed in 30 % of the cases, and intravenous coagula in 14 % of them. No frostbite was registered due to cold air blowing. Partial or total lesion improvement was obtained in 121 patients (86 %), with satisfactory cosmetic results. Unsatisfactory outcome was observed in 19 patients (14 %) due to no response or lesion worsening, thus crochet hook phlebectomy was indicated.Conclusion: CLaCS guided by Augmented Reality is a very effective option to treat telangiectasias, reticular and feeder veins. It is a safe method based on the employment of technology and an organic sclerosing agent. It dispenses the use of any other medication, thus being free of risk of anaphylaxis or embolism.
Keywords: Cryo-laser; cryo-sclerotherapy; varicosis